2004
DOI: 10.1212/01.wnl.0000145767.36287.a1
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin relieves symptoms of painful diabetic neuropathy

Abstract: In patients with diabetic peripheral neuropathy, pregabalin demonstrated early and sustained improvement in pain and a beneficial effect on sleep, which were confirmed by positive patient global impression. Pregabalin was well tolerated at all doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
333
8
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(381 citation statements)
references
References 27 publications
25
333
8
10
Order By: Relevance
“…The improvement in pain relief and sleep began during the first week of use. These results were confirmed in a separate, similar study completed by Lesser et al 86 in patients with DPN. In this study, however, both a 300 mg and 600 mg daily dose were shown to be superior to placebo, although there was no significant difference between the 300 and 600 mg/day dose.…”
Section: Pregabalinsupporting
confidence: 70%
“…The improvement in pain relief and sleep began during the first week of use. These results were confirmed in a separate, similar study completed by Lesser et al 86 in patients with DPN. In this study, however, both a 300 mg and 600 mg daily dose were shown to be superior to placebo, although there was no significant difference between the 300 and 600 mg/day dose.…”
Section: Pregabalinsupporting
confidence: 70%
“…There are seven double-blind, randomized, placebo-controlled trials in painful DPN with pregabalin (6 -12), five of which are published in full (7)(8)(9)(10)(11). The effective dosing range for treatment of neuropathic pain syndromes is 150 to 600 mg/day, administered either three times daily (TID) or twice daily (BID).…”
mentioning
confidence: 99%
“…Two other large clinical trials reported similar side-effect profiles. 12,13 More recently, a randomized, double-blind, placebo controlled trial showed that pregabalin (600 mg/day) was well-tolerated, and the adverse events were higher in the pregabalin arm. The most common adverse events due to pregabalin were, peripheral edema, dizziness, weight gain and somnolence.…”
Section: Discussionmentioning
confidence: 99%